Ar galima pasikliauti nauja skydliaukės masės ir tūrio skaičiavimo metodika - Astrauskas, Juozas Vincas (Lietuvos chirurgija, 2003)
Juozas Vincas AstrauskasE-mail: bio@me.vtu.ltBased on practical data of ultrasound diagnostics of thyroid gland, a new method of evaluating the volume and mass of the gland is proposed. The new method is based on a formal evaluation of the shape of the thyroid gland describing its parts as a symmetrical semiellipsoid of rotation. Several formulas for computing the volume and mass are proposed, the correction coefficients for volume and mass have been obtained. The coefficients only insignificantly differ from those proposed in earliest sources.The main inaccuracies of the approach are the following:    1. The proposed method cannot account for the asymmetrical shape of thyroid gland lobules. More correctly they could be described as an asymmetrycal paraboloid of rotation along A axis (or semiellipsoid of rotation).The more exact formulas for computing are proposed.    2. The inaccuracies in contouring the shape of the lobules can cause additional faults in the results.In conclusion, this method computation can be applied for an approximate evaluation of the volume and mass of thyroid gland for extra diagnosis during ultrasound screening.